Analysis Of Aerial Photography With Drone Type Fixed Wing In Kotabaru, Lampung - Indreswari Suroso; Erwhin Irmawan (Politeknik Negeri Batam, 2018)
In the world of photography is very closely related to the unmanned aerial vehicle called drones. Drones mounted camera so that the plane is pilot controlled from the mainland. Photography results were seen by the pilot after the drone aircraft landed. Drones are unmanned drones that are controlled remotely. Unmanned Aerial Vehicle (UAV), is a flying machine that operates with remote control by the pilot. Methode for this research are preparation assembly of drone, planning altitude flying, testing on ground, camera of calibration, air capture, result of aerial photos and analysis of result aerial photos. There are two types of drones, multicopter and fixed wing. Fixed wing has an airplane like shape with a wing system. Fixed wing use bettery 4000 mAh . Fixed wing drone in this research used mapping in This drone has a load ability of 1 kg and operational time is used approximately 30 minutes for an areas 20 to 50 hectares with a height of 100 m to 200 m and payload 1 kg above ground level. The aerial photographs in Kotabaru produce excellent aerial photographs that can help mapping the local government in the Kotabaru region.